2022
DOI: 10.1007/s10522-022-09990-x
|View full text |Cite
|
Sign up to set email alerts
|

Predation stress experienced as immature mites extends their lifespan

Abstract: The early-life experience is important in modulating the late-life performance of individuals. It has been predicted that there were trade-offs between early-life fitness and late-life success. Most of the studies on senescence have focused on the trade-offs between the reproduction and lifespan, and the influences of diet, mating, and other factors. Because the negative, non-consumptive effects of predators could also modulate the behaviour and underlying mechanisms of the prey, this study aimed to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 91 publications
0
5
1
Order By: Relevance
“…Another of our studies (Wei et al. , 2022 in preparation) showed that predation stress given during the entire immature period (about 12–16 d) increased the lifespan of both male and female by 9.7% on average, whereas prey exposure to predation stress during their oviposition and post‐oviposition periods reduced their lifespans by 24.8% and 28.7%, respectively. The patterns in survival rates among different treatments in our studies showed broadly similar trends in data on lifespan.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Another of our studies (Wei et al. , 2022 in preparation) showed that predation stress given during the entire immature period (about 12–16 d) increased the lifespan of both male and female by 9.7% on average, whereas prey exposure to predation stress during their oviposition and post‐oviposition periods reduced their lifespans by 24.8% and 28.7%, respectively. The patterns in survival rates among different treatments in our studies showed broadly similar trends in data on lifespan.…”
Section: Discussionmentioning
confidence: 56%
“…To test the hypothesis of Wei and Zhang's (2022) that milder levels of predation stress might have no effect on prey lifespan or even increase it, Wei et al. (2022) reduced the duration of exposure to predation stress and showed that predation stress applied only during immature development could increase lifespan (by 9.7%), although, it is not clear if the benefits of this “milder” predation stress resulted from the short duration of exposure or from the early life exposure. This study therefore further reduced the duration of exposure to predation pressure during the early part of prey life history and demonstrated that only the very early stages (larva and protonymph) responded positively to predation stress and therefore extended lifespan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we discovered that the impact of predation risk on prey B. dorsalis development time was gender-specific; female B. dorsalis treated with isolated predator had a shorter development time than those in the control treatment, while this was not observed in males. This disparity was also found in the phytophagous mite (Tyrophagus putrescentiae), where regardless of being subjected to predator stress throughout the life cycle or at different life stages, the lifespan of males was significantly longer than that of females [22]. The variation in development time responses between females and males could be attributed to the fact that females bear the responsibility for fecundity and need to allocate most of their resources to reproduction, leaving less for development under predation risks [48,50,51].…”
Section: Discussionmentioning
confidence: 90%
“…Long-term exposure to predation threat, such as that of the six-spotted ladybug (Menochilus sexmaculatus), significantly reduces the lifespan of adult cotton aphids (Aphis gossypii) [21]. In the case of the herbivorous mite (Tyrophagus putrescentiae), individuals in control conditions exhibit a significantly longer lifespan than those subjected to predation risk, regardless of whether the stress occurs throughout their entire life cycle or only at specific stages [22]. The duration of predation risks also affects lifespan; adult Drosophila melanogaster experiences a significantly shorter lifespan under continuous predation risk from ladybugs (Propylea japonica) compared to those facing intermittent risk [23].…”
mentioning
confidence: 99%